FAKTOR-FAKTOR YANG MEMPENGARUHI PENGELUARAN RUMAH TANGGA PEKERJA WANITA YANG BEKERJA DI INDUSTRI LAUNDRY RUMAH TANGGA DI KECAMATAN DENPASAR SELATAN - Rosiana, Wiji; Saskara, Ida Ayu Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.11.TAHUN 2018DO - 10.24843/EEB.2018.v07.i11.p02, 2018)
Rapid economic growth has resulted in the emergence of small, medium, and large industries. One of the fastest growing industries is the household laundry industry, where most of the workers are women. The purpose of this research are: 1) To analyze the effect of education level, worker's wage, husband's income, age, number of family dependent and working hours directly to household expenditure; 2) To analyze the effect of education level, worker's wage, husband's income, age and amount of family dependent on household expenditure through working hours. Data collection methods used were interviews and questionnaires, with a total of 87 respondents. The analytical tool used is descriptive analysis and path analysis. The results showed that the level of education, worker's wage and husband's income had a positive significant impact on the working hours of female workers. Age negatively significantly affects the working hours of female workers. The number of family dependents has a positive insignificant effect on the working hours of female workers. Worker's wage, husband's income, the number of family dependents and working hours have a positive significant impact on the expenditure of female workers' households. The level of education and age has a negative insignificant effect on the expenditure of female workers' households. Working hours mediate the influence of education level, the influence of the wage of the worker, the husband's income and age on the expenditure of the female worker's household. While working hours do not mediate the number of family dependents on household expenditure of female workers working in the household laundry industry in South Denpasar District.